Cleavage of Occludin by Cigarette Smoke-Elicited Cathepsin S Increases Permeability of Lung Epithelial Cells - Paul Bigot; Simon Chesseron; Ahlame Saidi; Damien Sizaret; Christelle Parent; Agnès Petit-Courty; Yves Courty; Fabien Lecaille; Gilles Lalmanach (MDPI AG, 2022)
Background. Chronic obstructive pulmonary disease (COPD) is an irreversible disease mainly caused by smoking. COPD is characterized by emphysema and chronic bronchitis associated with enhanced epithelial permeability. Hypothesis. Lung biopsies from smokers revealed a decreased expression level of occludin, which is a protein involved in the cohesion of epithelial tight junctions. Moreover, the occludin level correlated negatively with smoking history (pack-years), COPD grades, and cathepsin S (CatS) activity. Thus, we examined whether CatS could participate in the modulation of the integrity of human lung epithelial barriers. Methods and results. Cigarette smoke extract (CSE) triggered the upregulation of CatS by THP-1 macrophages through the mTOR/TFEB signaling pathway. In a co-culture model, following the exposure of macrophages to CSE, an enhanced level of permeability of lung epithelial (16HBE and NHBE) cells towards FITC-Dextran was observed, which was associated with a decrease in occludin level. Similar results were obtained using 16HBE and NHBE cells cultured at the air-liquid interface. The treatment of THP-1 macrophages by CatS siRNAs or by a pharmacological inhibitor restored the barrier function of epithelial cells, suggesting that cigarette smoke-elicited CatS induced an alteration of epithelial integrity via the proteolytic injury of occludin. Conclusions. Alongside its noteworthy resistance to oxidative stress induced by cigarette smoke oxidants and its deleterious elastin-degrading potency, CatS may also have a detrimental effect on the barrier function of epithelial cells through the cleavage of occludin. The obtained data emphasize the emerging role of CatS in smoking-related lung diseases and strengthen the relevance of targeting CatS in the treatment of emphysema and COPD.